Universal Stress Proteins Are Important for Oxidative and Acid Stress Resistance and Growth of Listeria monocytogenes EGD-e In Vitro and In Vivo - Seifart Gomes, Christa; Izar, Benjamin; Pazan, Farhad; Mohamed, Walid; Mraheil, Mobarak Abu; Mukherjee, Krishnendu; Billion, André; Aharonowitz, Yair; Chakraborty, Trinad; Hain, Torsten (PloS one, 2011)
Pathogenic bacteria maintain a multifaceted apparatus to resist damage caused by external stimuli. As part of this, the universal stress protein A (UspA) and its homologues, initially discovered in Escherichia coli K-12 were shown to possess an important role in stress resistance and growth in several bacterial species. We conducted a study to assess the role of three homologous proteins containing the UspA domain in the facultative intracellular human pathogen Listeria monocytogenes under different stress conditions. The growth properties of three UspA deletion mutants (Δlmo0515, Δlmo1580 and Δlmo2673) were examined either following challenge with a sublethal concentration of hydrogen peroxide or under acidic conditions. We also examined their ability for intracellular survival within murine macrophages. Virulence and growth of usp mutants were further characterized in invertebrate and vertebrate infection models. Tolerance to acidic stress was clearly reduced in Δlmo1580 and Δlmo0515, while oxidative stress dramatically diminished growth in all mutants. Survival within macrophages was significantly decreased in Δlmo1580 and Δlmo2673 as compared to the wild-type strain. Viability of infected Galleria mellonella larvae was markedly higher when injected with Δlmo1580 or Δlmo2673 as compared to wild-type strain inoculation, indicating impaired virulence of bacteria lacking these usp genes. Finally, we observed severely restricted growth of all chromosomal deletion mutants in mice livers and spleens as compared to the load of wild-type bacteria following infection. This work provides distinct evidence that universal stress proteins are strongly involved in listerial stress response and survival under both in vitro and in vivo growth conditions.